Parathyroid surgery : fundamental and advanced concepts - Terris, David J.; Duke, William S.; Pasieka, Janice (Plural Publishing, Inc., 2014)
With worldwide contributions from experts in the field of parathyroid disease and surgery, this is the only text devoted specifically to the surgical management of parathyroid disease. Chapters include detailed discussions of preoperative diagnosis and testing, advanced imaging techniques and state-of-the-art surgical interventions, and incorporate thorough and judicious reviews of the current medical literature. Postoperative management strategies are also addressed to ensure physicians can safely optimize patient outcomes.